2019
DOI: 10.1109/access.2019.2914368
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Analysis of Open Source Software (OSS) Usability for Sustainable OSS Product

Abstract: The increase in the number of open source software (OSS) users have drawn attention to improving usability. Usability is a clear concept that encompassing both task and user characteristics as well as functionality. Usability is an essential factor that affects user acceptance and OSS sustainability, which is considered as the key to the success of the OSS. To some extent, usability is one concern of the larger issue of system acceptability and sustainability. Therefore, usability is an important factor that n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Saaty was the first to propose the AHP process [41]. AHP process utilizes only the matrix of the pair-wise analysis to tackle the inaccuracy in challenges of decision labeling in multi-criteria [42].…”
Section: Fuzzy Ahpmentioning
confidence: 99%
“…Saaty was the first to propose the AHP process [41]. AHP process utilizes only the matrix of the pair-wise analysis to tackle the inaccuracy in challenges of decision labeling in multi-criteria [42].…”
Section: Fuzzy Ahpmentioning
confidence: 99%
“…The AHP process was first proposed by Saaty [39]. It only uses the pair-wise comparison matrix to handle the imprecision in multi-criteria decision marking problems [18]. The model proposed here uses the triangular fuzzy numbers for representing the linguistic variables and implementing fuzzy operations with AHP.…”
Section: Integrated Fuzzy Ahp-topsis Methodsmentioning
confidence: 99%
“…• Dawood et al [18] in 2018 presented an article on sustainable design of web applications. The authors provided the principles and viewpoints on sustainability with respect to web application security for providing a situation and methodology on web application design and sustainability.…”
Section: Related Workmentioning
confidence: 99%
“…Usability tests have led to some research sensitivity. In the research (Dawood et al, 2019), usability refers to software sustainability. The same authors found that the usability of the system influences the acceptance of users to adopt an information system, as well as its sustainability.…”
Section: Factors Affecting the Adoption Of Technologymentioning
confidence: 99%